OUTPUT: Choreographed and Reconfigured Human and Industrial Robot Bodies Across Artistic Modalities - Cuan, Catie (Frontiers in Robotics and AI, 2021)
Millions of industrial robots are used across manufacturing and research applications worldwide. Handfuls of these robots have been used in dance, installation, and theatrical art works as tools and performers. OUTPUT, a collaborative artwork presented here, employs an industrial robot as choreographic source material and dancing body in order to reframe these robots as performers and bring them into closer proximity with the general public. This OUTPUT work has existed as a performance, installation, and augmented reality application. All three formats of the work include improvisational components, where a human can dance with a representation of themselves alongside an industrial robot, and thus have an embodied and creative experience next to these sequestered machines.